Games to increase physical activity in inactive university students in their school day/Juegos para incrementar la actividad física en estudiantes universitarios inactivos en su jornada escolar - Osmany Aguero Fuentes; Yidier Pons Gámez; Yoanni Gil López; Rafael Ernesto Licea Mojena (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The present research was carried out at the "Jesús Montané Oropesa" University, with the objective of assessing the effect of the implementation of recreational games to increase physical activity in inactive university students during their school day. Theoretical methods were used, among which we can mention analysis and synthesis, induction-deduction and historical-logical. The empirical methods used were observation, document review, survey and opinion poll. Measurement was used as a technique for data collection. The SPS statistical-mathematical package was also used to process the information. As a result of this work, a compendium of games was achieved that will allow to solve the main deficiencies identified in the diagnosis and, in a continuous way, to increase the levels of physical activity in inactive university students during their school day.